Integrasi Sistem Monitoring Pengemasan Document Security dengan Barcode Berbasis Web - Shintania, Mira; Wiyanto, Wiyanto; Sanudin, Sanudin (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
Rapid technological developments demand innovation and creativity in utilizing and creating new solutions. This also applies to PT Xyz, which is facing digital transformation to integrate its systems. One of the challenges faced is that the packaging monitoring process is still carried out manually using queries on the database, causing limited access and lack of work efficiency Since the only individual with access to the database is the IT division. Research was carried out to build a web-based platform intended for monitoring packaging processes results using barcode numbers where there are 3 packages used, namely small cover, large cover and box cover. This system was developed using the waterfall methodology and SQL Server for the database. It aims to simplify data access for employees, reducing their dependence on the IT department, and enhance the accuracy and efficiency of their workflow by allowing direct data monitoring. Unified Modeling Language (UML) was utilized for system design modeling. The research outcomes include the integration of the packaging monitoring system with current packaging applications. Blackbox testing was employed, and the results confirmed that the barcode-based packaging monitoring system operated correctly without any errors.